Development of a System of Standard Designs in Industrial Construction - Silka, Dmitriy; Butyrin, Andrey (E3S web of conferences, 2021)
The use of standard designs in construction is a topical subject of research within the frame of project management. Construction projects, especially industrial construction ones, are characterized by a great diversity of design and other solutions. Just about any new project produces new ways of resolving issues and involves looking for optimum constructive, planning, and other solutions. There arises the need to coordinate all parts of the work with the client, although essentially there is nothing particularly novel about the project, as many of the issues were already resolved in past activity. Quite naturally, many construction companies will look for tried-and-true solutions and strive for the unification and standardization of design work. This paper describes a set of tools for implementing a system of standard designs and proposes a set of ways to achieve one’s key design objectives.